When the going gets tough, what happens to quiet eye? The role of time pressure and performance pressure during basketball free throws. (January 2022) - Giancamilli, Francesco; Galli, Federica; Chirico, Andrea; Fegatelli, Dario; Mallia, Luca; Palombi, Tommaso; Cordone, Susanna; Alivernini, Fabio; Mandolesi, Laura; Lucidi, Fabio
Abstract: In aiming sport contexts, the quiet eye (QE) - the final ocular fixation before movement initiation - is a crucial perceptual-cognitive skill. Indeed, an extended QE permits athletes to achieve high performances, aiding optimal attentional control, particularly in situations in which athletes are "under pressure." Such situations are common in sport, especially when time runs out, and even just a few points can mean the difference between victory and defeat. Although QE has been widely investigated across several sports and tasks, no previous studies have considered both the role of time pressure and performance pressure on QE. The current study aimed to comprehend the effect of tough sport situations on QE characteristics. Accordingly, we tested basketball players (competitive-élites and semi-élites) in free throw trials, manipulating both the time available to perform the task and the relevance of the performance. The results showed that time pressure and performance pressure impaired QE characteristics, regardless of expertise levels. Also, time pressure led to a decrease in free throw accuracy. Interestingly, the match between task demands and the ability to cope seemed to play a role on QE, especially in the competitive-élite players, with negative QE characteristics (short and late) when task demands exceeded the ability to cope. These findings suggest that QE research and QE training protocols should account for time pressure, performance pressure, and the players' perceived ability to cope with the requested task. Highlights: Literature showed that an early and extended quiet eye (QE) is a relevant gaze feature that characterize an optimal attentional and visuomotor control during aiming tasks. The perceived ability to cope with task demands seems a variable that influences QE characteristics. The current study reported the QE characteristics (onset and duration) of players during a self-paced task (free throw) performed in both comfortable and harsh trials. The current results showed that players performed a poor attentional control (short and late QE) in free throws in which task demands exceeded the ability to cope. The current findings suggest adding tough conditions to existing QE trainings to increase performances in hard game contexts.